PENGARUH MODIFIKASI PEMBELAJARAN BOLA VOLI TERHADAP HASIL BELAJAR PASSING BAWAH PADA PESERTA DIDIK SMA - Grada, Marselina; Simanjuntak, Victor G; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem taken in this study is whether there is a modification effect of volleyball learning on the results of learning to pass under at class X Pontianak 3 State Senior High School. The purpose of this study was to determine the effect of learning modification on the results of learning to pass under volleyball.The population in this study is class X as many as 4 classes with a total of 152 students. Sampling in this study using purposive sampling technique, which amounted to 38 students as an experimental class. The method used in this study is an experiment with pre experimental design. Based on the results of the t-test in the experimental class, the t_count ≥ t_ (table) is 7.9 ≥ 1.687, so H0 is rejected (Ha is accepted), it means that there is a modification effect on volleyball learning on the results of learning under passing on students in class X SMA 3 Pontianak , with a percentage of influence of 31.53%. Keywords: Modification, Learning Outcomes, Passing Down